On the Comparative Study of Christianity and Daoism by Christian Scholars in the Early 20th Century - XU, Tao (Journal of Research for Christianity in China (JRCC), 2026)
In the early 20th century, driven by the "Anti-Christian Movement" and the wave of national awakening, some Chinese Christian scholars began to pay attention to the comparison between Christianity and Daoism in order to promote the integration of Christianity with Chinese culture. Through methods such as cross-textual interpretation, they attempted to explore the construction of a Christian theological framework with distinctive Chinese cultural characteristics. At the same time, some more open-minded missionaries in China gradually abandoned their earlier prejudices against Daoism and expanded the scope of comparative studies between Christianity and Daoism from pre-Qin Daoist philosophy to the later canonical doctrines, rituals, and practices of religious Daoism. Although these studies were often limited by forced interpretations and insufficient engagement with practical concerns, their contribution lies in initiating preliminary attempts at equal dialogue between Christianity and Daoism, broadening the field and approaches of comparative research, and providing important theoretical resources and historical references for the sinicization of Christian thought.